(untitled) (The Peerian Journal, 2024)
This article explores South Korea, Japan, and China’s cultural diplomacy strategies and their impact on the development of soft power in East Asia. It delves into South Korea’s dynamic K-pop industry, its global appeal through social media, and the transformative Korean Wave (Hallyu) that has reshaped international perceptions. South Korea leverages pop culture to enhance its global image. In contrast, Japan’s cultural diplomacy, rooted in post-World War II traditions, has evolved to include internationally acclaimed entertainment like anime and video games. China, with its unique communist regime, blends Hollywood collaborations with economic influence and infrastructure development to bolster its soft power. The article highlights these countries’ diverse strategies in cultural diplomacy while recognizing its pivotal role in shaping global opinions and promoting cultural diversity. The main objective is to elucidate how these nations harness their cultural assets to enhance their global influence and soft power, shedding light on the significance of cultural diplomacy in contemporary international relations.